Prioritizing Disaster Risks for Post-Disaster Permanent Housing Relocation in Palu, Indonesia: An Analytic Hierarchy Process (AHP) Approach - Andi Asnudin; Amar Akbar Ali; Tutang Muhtar Kamaludin; Andi Rizal; William Arrang Sarungallo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study employs the Analytic Hierarchy Process (AHP) to conduct a technical evaluation of disaster risk in the selection of sites for Permanent Housing (HUNTAP) for survivors of the 2018 earthquake, tsunami, and liquefaction disaster in Palu, Central Sulawesi. The analysis integrates five main disaster criteria (floods, landslides, tsunamis, earthquakes, and liquefaction) and 31 sub-criteria compiled from literature and expert judgment. The AHP results show that flood risk is the dominant factor in relocation decisions (relative weight 47.07%), followed by landslides (23.85%), tsunamis (12.52%), earthquakes (11.19%), and liquefaction (5.38%). Key sub-criteria such as lowland areas, river border zones, and drainage conditions are the most significant flood risk indicators. This research provides a structured, multi-criteria decision-making framework to ensure that post-disaster relocation prioritizes the most critical hazards, thereby enhancing the safety and sustainability of settlements in complex disaster-prone regions like Palu. The findings recommend targeted, risk-based mitigation strategies for each hazard priority.